Economic integration and the exchange rate regime: How damaging are currency crises? - Axel A. Weber; Günter W. Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We use consumer price data for 205 cities/regions in 21 countries to study PPP deviations before, during and after the major currency crises of the 1990s. We combine data from industrialized nations in North America (Unites States, Canada and Mexico), Europe (Germany, Italy, Spain and Portugal), Asia (Japan and South Korea), and Oceania (Australia and New Zealand) with corresponding data from emerging market economies in South America (Argentina, Bolivia, Brazil, Columbia) and Asia (India, Indonesia, Malaysia, Philippines, Taiwan, Thailand). By doing so, we confirm previous results that both distance and border explain a significant amount of relative price variation across different locations. We also find that currency attacks had major disintegration effects by considerably increasing these border effects and by raising within-country relative price dispersion in emerging market economies. These effects are found to be quite persistent since relative price volatility across emerging markets today is still significantly larger than a decade ago.
urn:nbn:de:hebis:30-9909
Keywords: F40; F41; 330; relative price volatility; spatial data; real exchange rate volatility; law of one price; purchasing power parity; currency crisis; contagion